OVERTRAINING AS A RISK FACTOR FOR ANTERIOR CRUCIATE LIGAMENT RUPTURE IN FEMALE BASKETBALL PLAYERS. Issue 4 (1st February 2017) - Stojmenovic, Tamara; Malic, Tatjana; Vukasinovic-Vesic, Milica; Andjelkovic, Marija; Dikic, Nenad
Abstract : Background: High incidence of anterior cruciate ligament (ACL) tears among female basketball players requires a proper understanding of the risk factors in order to reduce the number of these severe events. Objective: It was hypothesized that athletes involved in professional level of basketball and more than 10 hours of training per week at young age are exposed to greater risk of ACL rupture due to overtraining. Design: Non-experimental correlation retrospective study was performed. Setting: In order to collect data Serbian female basketball players, from both domestic and European professional teams, were contacted. Patients (or Participants): A total of 108 female basketball players were included in the study (age 26.26±6.8). Interventions (or Assessment of Risk Factors): The questionnaire regarding the involvement in a professional level of basketball and hours/week of training at younger age was administrated to participants. The logistic regression method was used in order to calculate the odds ratio confidence interval (O. R.). Main Outcome Measurements: The athletes exposed to high intensity and frequency of training had grater odds of getting ACL rupture. Results: 43 out of 108 athletes reported ACL injury at the age of 18.25±3.12. Those involved in professional level of basketball had an odds of ACL injury about 9.25 times greater than those who competed only for their age group (OR 9.2503; p=0.0001). The ones exposed to more than 10 hours of training per week had an odds of ACL injury about 7.54 greater than those with less training hours (O R 7.5374; p=0.0002). Conclusions: Playing basketball at a professional level at younger age can lead to overtraining and consequently an increased incidence of ACL ruptures in female basketball players. Accordingly, intensity and frequency of training must be adapted to both chronological and biological age of young athletes in order to prevent this serious injury.